Harmonisasi pancasila dan hak asasi manusia dalam menjaga persatuan bangsa - Warokhmah, Nabila Syawal (Maliki Interdisciplinary Journal, 2025)
This study explores the harmonization of Pancasila as Indonesia’s state ideology with Human Rights (HAM) as a crucial factor in maintaining the unity of a diverse nation. It discusses how Pancasila’s values, particularly the principle of unity, align with universal human rights principles to prevent social fragmentation. Employing a qualitative literature review, the research demonstrates that the integration of these values fosters tolerance and inclusivity, which are essential in sustaining national cohesion. The research highlights that education and social practices grounded in Pancasila and human rights nurture nationalism and respect for Indonesia’s diverse cultures. This harmonization is exemplified by conflict resolution efforts in Papua and national education programs that cultivate respect for tolerance and human rights, illustrating a practical approach to safeguarding social harmony and national progress. This unity strengthens mutual respect and inclusiveness, which underpins patriotism and prevents social division. Education that integrates the values ​​of Pancasila and human rights is crucial for fostering tolerance and respect for diversity from an early age.